2019
DOI: 10.1021/acs.jpcc.9b07441
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitrogen on the Mechanical Properties of the Novel Carbon Nitride Nanothreads

Abstract: Carbon nanothread (C-NTH) is a new ultrathin one-dimensional sp3 carbon nanostructure, which exhibits promising applications in novel carbon nanofibers and nanocomposites. Recently, researchers have successfully developed a new alternative structureultrathin carbon nitride nanothread (CN-NTH). In this work, we investigate the mechanical properties of CN-NTHs through large-scale molecular dynamics simulations. Comparing with their C-NTH counterparts, CN-NTHs are found to exhibit a higher tensile and bending st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Here, ρ is the curvature and D is the bending stiffness. Based on the nonlinear least square fitting, the bending stiffness is derived as 3635 and 3688 eV Å for the D-AB sample along the armchair and zigzag directions, respectively, which is much higher than the 1D sp 3 carbon nanothreads (less than 100 eV·Å). , Based on the approach given in ref , that is, E b / N = 1/2 D *ρ 2 ( N is the atom number and D * is the normalized bending stiffness of per atom), the graphene sheet has a bending stiffness of 3.43 eV Å 2 and diamane shows an order of higher normalized bending stiffness in both armchair (41.26 eV Å 2 ) and zigzag directions (41.30 eV Å 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, ρ is the curvature and D is the bending stiffness. Based on the nonlinear least square fitting, the bending stiffness is derived as 3635 and 3688 eV Å for the D-AB sample along the armchair and zigzag directions, respectively, which is much higher than the 1D sp 3 carbon nanothreads (less than 100 eV·Å). , Based on the approach given in ref , that is, E b / N = 1/2 D *ρ 2 ( N is the atom number and D * is the normalized bending stiffness of per atom), the graphene sheet has a bending stiffness of 3.43 eV Å 2 and diamane shows an order of higher normalized bending stiffness in both armchair (41.26 eV Å 2 ) and zigzag directions (41.30 eV Å 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The C–C and C–H atomic interactions were described by the widely used adaptive intermolecular reactive empirical bond order (AIREBO) potential, which can accurately capture the bond interaction, breaking, and formation . The cutoff distance was modified to 2.0 Å to avoid the nonphysical phenomenon during the fracture process. , Previous works have shown that AIREBO can well reproduce the fracture behaviors of graphene, CNT, , and carbon nanothreads (with sp 3 bonds). , …”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last decade was characterized by a revived interest for low-dimensional carbon materials that can be obtained by pressure-induced polymerization of aromatic hydrocarbons, with particular attention to a class of saturated carbon compounds having a structure resembling a unidimensional diamond-like wire. These materials, generally called saturated carbon nanothreads, potentially possess extraordinary mechanical properties, being extremely flexible and resilient and preserving most of the tensile strength of the diamond, and are extremely attractive from a technological point of view. These properties can be suitably tuned by controlling the thread length, the type and concentration of defects, and the presence of heteroatoms or functional groups, while preserving most of the mechanical properties. ,, …”
Section: Introductionmentioning
confidence: 99%
“…They performed MD simulations to investigate their dynamic characteristics, and the results showed that DNT-based nano-mass sensors have an excellent mass resolution of g, which is higher than those of CNTs- or GSs-based nano-mass sensors. Recently, there were some nanothreads that were produced by different methods, such as one-dimensional carbon nanothreads through modest-pressure polymerization of Furan [ 16 ], orientational order in nanothreads derived from thiophene [ 17 ], one-dimensional diamondoid polyaniline-like nanothreads from compressed crystal aniline [ 18 ], double core chromophore-functionalized nanothreads by compressing azobenzene [ 19 ], and carbon nitride nanothreads [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%